2001
DOI: 10.1155/mbd.2001.65
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Some New Ru(III) Complexes Using aryl‐azo Pentane‐2,4‐dione and 2,6‐bis (2′‐Benzimidazolyl) Pyridine as Ligands:Synthesis, Spectroscopic, Luminescent, Electrochemical and Biological Activities

Abstract: Some ruthenium(III) complexes with aryl-azo 2,4-pentanedione as co-ligands (L1H - L3H2) have been synthesized and characterized spectroscopically IR, 1H NMR, UV/Vis, ESR, conductimetric) along with elemental analysis and FAB-mass data. Their luminescent and redox properties have been studied. The antibacterial, anti-HIV and antitmnour activities have also been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…In the complexes lowering of m(C@O) from 1668-1676 to 1644-1655 cm À1 indicated that pentanediones had coordinated with Ru(II) ion. Additional peaks observed at 1604-1606 and 760-665 cm À1 due to skeletal and d(C-H) out of plane deformation modes of bpy, respectively and at 842-844 cm À1 due to m(P-F) mode of PF À 6 ions were consistent with early reports [15][16][17][18]. In the 1 H NMR spectra of the complexes no peaks due to OH or NH protons were observed which indicated that the deprotonated ligands coordinated to the metal ions.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the complexes lowering of m(C@O) from 1668-1676 to 1644-1655 cm À1 indicated that pentanediones had coordinated with Ru(II) ion. Additional peaks observed at 1604-1606 and 760-665 cm À1 due to skeletal and d(C-H) out of plane deformation modes of bpy, respectively and at 842-844 cm À1 due to m(P-F) mode of PF À 6 ions were consistent with early reports [15][16][17][18]. In the 1 H NMR spectra of the complexes no peaks due to OH or NH protons were observed which indicated that the deprotonated ligands coordinated to the metal ions.…”
Section: Resultssupporting
confidence: 91%
“…Analytical and FAB (fast atom bombardment) mass data as well as other physical properties of the complexes are listed in Table 1. The specific conductance (Table 1) of the complexes recorded in acetonitrile solution (10 À3 M) were found to be consistent with the earlier reports [15][16][17][18].…”
Section: Resultssupporting
confidence: 90%
“…These complexes possess a diversity of coordination modes including different isomeric types and oligomeric compounds [5,6]. Some of them reveal good catalytic effects [7,8] and remarkable biological activities [9,10]. However, in spite of extensive work, only a few fully structurally characterized ruthenium b-diketonate complexes containing phosphines have been published, so far [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[31] In addition, the higher spectrum of the PF 6 salts of each complex showed a strong band at 756 cm −1 and 750 cm −1 ascribable to the counter anion and this band was absent for the corresponding chloride salts. [32] The Co(III) complex was found to be octahedral geometry and diamagnetic where as Fe(II) complex was found to be square planar geometry and paramagnetic.…”
Section: -Methylquinoline and [1-{[2-{[2-hydroxynaphthalen-1-yl)methmentioning
confidence: 96%